2017
DOI: 10.1093/gerona/glw251
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Alzheimer’s Disease: A Systematic Review

Abstract: The current literature includes several studies investigating the association between physical activity and risk of Alzheimer's disease (AD). The aim of this review was to systematically evaluate available evidence on this association. Medline via PubMed and CINAHL databases were searched for original English language research articles assessing the relationship between physical activity and incident AD. The review was limited to prospective observational and intervention studies. Criteria for exclusion were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
143
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(157 citation statements)
references
References 60 publications
5
143
0
9
Order By: Relevance
“…Delaying the onset of this failure might delay the onset of Alzheimer's disease. At present, physical exercise that maintains vascular health is one of the few potential protective treatments available for LOAD [55][56][57][58]. Indeed, a recent systematic review has revealed for the first time an association between physical exercise and better cognitive outcomes at expected symptom onset in individuals with fAD [59].…”
Section: Discussionmentioning
confidence: 99%
“…Delaying the onset of this failure might delay the onset of Alzheimer's disease. At present, physical exercise that maintains vascular health is one of the few potential protective treatments available for LOAD [55][56][57][58]. Indeed, a recent systematic review has revealed for the first time an association between physical exercise and better cognitive outcomes at expected symptom onset in individuals with fAD [59].…”
Section: Discussionmentioning
confidence: 99%
“…98 Building on the connection between heart health and brain health, researchers have found that factors that protect the heart may also protect the brain and reduce the risk of developing Alzheimer's or other dementias. Physical activity [115][116][117][118][119][120][121][122][123][124][125] appears to be one of these…”
Section: Cardiovascular Disease Risk Factorsmentioning
confidence: 99%
“…Emerging evidence shows that exercise and physical activity may have positive effects on cognitive and physical function in older adults with CI and dementia [2-5]; however, low adherence has been reported [6, 7]. The chief reasons for nonadherence included a low willingness to continue (35%) and behavioral disorders (40%).…”
Section: Introductionmentioning
confidence: 99%